2014
DOI: 10.1074/jbc.m113.522110
|View full text |Cite
|
Sign up to set email alerts
|

T-cell Receptor (TCR)-Peptide Specificity Overrides Affinity-enhancing TCR-Major Histocompatibility Complex Interactions

Abstract: Background: TCR recognition of bipartite ligands composed of self (MHC) and non-self (peptide) maintains T-cell specificity.Results: Mutation of residues in the cognate peptide override TCR mutations that enhance MHC binding.Conclusion: TCR-pMHC binding affinity requires specific TCR-peptide interactions.Significance: Stabilization of TCR-pMHC engagement by TCR-peptide interactions maintains T-cell specificity and prevents recognition of self-pMHC in the periphery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 63 publications
(101 reference statements)
3
59
0
Order By: Relevance
“…However, structural investigations of TCR-pMHC interactions have demonstrated that the TCR can establish a distinct and highly specific interaction with both peptide and MHC. In keeping with such specificity of binding requirements, even single mutations at key residues in the TCR, peptide, or MHC that are involved in the binding interface have been shown to abrogate antigen recognition (2529). The importance of T-cell cross-reactivity is manifest not only in effective immune surveillance (2, 8) but also in autoreactivity (30) and the design of therapeutics (10, 11).…”
Section: Discussionmentioning
confidence: 99%
“…However, structural investigations of TCR-pMHC interactions have demonstrated that the TCR can establish a distinct and highly specific interaction with both peptide and MHC. In keeping with such specificity of binding requirements, even single mutations at key residues in the TCR, peptide, or MHC that are involved in the binding interface have been shown to abrogate antigen recognition (2529). The importance of T-cell cross-reactivity is manifest not only in effective immune surveillance (2, 8) but also in autoreactivity (30) and the design of therapeutics (10, 11).…”
Section: Discussionmentioning
confidence: 99%
“…4). Arg65 forms a charge-charge interaction with a Glu or Asp near the end of CDR2β in 4 of the 13 complexes, as well as a fifth crystallized with an engineered TCR (42). Three other TCRs use a Glu or Asp at the start of CDR1α to interact with Arg65.…”
mentioning
confidence: 99%
“…Although there are not yet enough published TCR‐pMHC structures to fully answer these questions, there are a number of examples that demonstrate that the system works under a high level of peptide specificity. Indeed, our own recent observations show that TCR‐peptide specificity is maintained even in the presence of affinity‐enhancing TCR‐MHC interactions . We further demonstrated that single amino acid substitutions in the MHC‐bound peptide, that had a minimal structural impact, could substantially reduce TCR binding indirectly by altering solvent interactions during binding .…”
Section: Introductionmentioning
confidence: 51%